Karać czy zasądzać — dylematy towarzyszące odpowiedzialności karnej za zniesławienie - Kotas, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The Polish debate concerning the appropriate scope of freedom of expression and freedom of the press has a long history dating back almost 30 years. One of the crucial points in this debate is the criminal character of defamation in Poland. The text attempts to present the contemporary Polish legal regulations on defamation and also mentions some foreign solutions. The author analyses the normative notion of freedom of expres-sion in Polish constitutional circumstances and within the light of national and inter-national jurisprudence, concerning the limits of state intervention into the rights of free expression. The article postulates changes in the Polish regulations, at least the removal of restrictions and imprisonment from the Penal Code. Instead, the civil procedure shall be reformed to become friendlier and accessible for victims of violations of their per-sonal dignity and the public picture. The prospects for this to occur in the existing Polish political reality are rather doubtful.
Keywords: defamation; freedom of expression; Polish courts; art. 212 and 213 of the Polish Penal Code; chilling effect